Long-Term l-Serine Administration Reduces Food Intake and Improves Oxidative Stress and Sirt1/NFκB Signaling in the Hypothalamus of Aging Mice - Zhou, Xihong; Zhang, Haiwen; He, Liuqin; Wu, Xin; Yin, Yulong (Frontiers in Endocrinology, 2018)
Serine has recently been shown to reduce oxidative stress and inflammation, which, when occurring in the hypothalamus, contribute to age-related obesity. To explore whether long-term serine administration reduces oxidative stress and body weight in aging mice, various concentrations of l-serine dissolved in water were administered to 18-month-old C57BL/6J mice for 6 months. The results showed that the administration of 0.5% (w/v) l-serine significantly reduced food intake and body weight gain during the experiment. Moreover, the administration of 0.5% l-serine decreased the concentrations of leptin, malondialdehyde, interleukin-1β, and interleukin-6, while it increased those of superoxide dismutase and glutathione, in both the serum and hypothalamus. Reactive oxygen species and the activity of nicotinamide adenine dinucleotide phosphate oxidase were reduced in the hypothalamus of aging mice treated with l-serine as compared with untreated control mice. Additionally, the expression of the leptin receptor increased while the levels of neuropeptide Y and agouti-related protein decreased in mice that had been treated with 0.5% l-serine. The expression of Sirt1 and phosphorylated signal transducers and activators of transcription 3 (pSTAT3) increased, while that of phosphorylated NFκB decreased in the mice treated with 0.5% l-serine. These results indicated that long-term l-serine administration reduces body weight by decreasing orexigenic peptide expression and reduces oxidative stress and inflammation during aging in mice, possibly by modulating the Sirt1/NFκB pathway. Thus, l-serine has the potential to be used in the prevention of age-related obesity.